2023
DOI: 10.1002/hsr2.1751
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the holy Quran recitation and listening on anxiety, stress, and depression: A scoping review on outcomes

Khadijeh Moulaei,
Ali‐Akbar Haghdoost,
Kambiz Bahaadinbeigy
et al.

Abstract: Background and AimAnxiety, stress, and depressive disorders as common mental health problems have adverse effects in different populations. Holy Quran recitation and listening can help reduce these disorders. Therefore, the aim of this study was to investigate the effect of the Holy Quran on anxiety, stress, and depression.Materials and MethodsTo retrieve eligible studies, we searched PubMed, Web of Science, and Scopus databases. The articles were screened and chosen by three researchers. The selection of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
(155 reference statements)
0
1
0
Order By: Relevance
“…Another study, carried out by Moulaei et al. (2023) showed that Qur’anic recitation have reducing effect on anxiety, stress and depression ( 30 ). There is still none any longitudinal study pointing out the Qur’anic repetition in a prayer could have effect on childhood group, nonetheless it is hypothetically valid and worth examining.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, carried out by Moulaei et al. (2023) showed that Qur’anic recitation have reducing effect on anxiety, stress and depression ( 30 ). There is still none any longitudinal study pointing out the Qur’anic repetition in a prayer could have effect on childhood group, nonetheless it is hypothetically valid and worth examining.…”
Section: Introductionmentioning
confidence: 99%